The bomb’s imagem - Murari, Lucas (Farol, 2024)
This article seeks to investigate the imagery production surrounding the atomic bomb, especially its first detonation, the Trinity Experiment. It was carried out as a test on United States soil, a few weeks before the bombings in Hiroshima and Nagasaki. This is a study that also aims to analyze the way in which the experiment was communicated by the country’s government, as well as its reception among the population.